Impact of Tumor Burden Score on Conditional Survival after Curative-Intent Resection for Hepatocellular Carcinoma: A Multi-Institutional Analysis - Elfadaly, AN (2021)
Background: The impact of tumor burden score (TBS) on conditional survival (CS) among patients undergoing curative-intent resection of hepatocellular carcinoma (HCC) has not been examined to date. Methods: Patients who underwent liver resection of HCC between 2000 and 2017 were identified from a multi-institutional database. The impact of TBS and other clinicopathologic factors on 3-year conditional survival (CS3) was examined. Results: Among 1,040 patients, 263 (25.3%) patients had low TBS, 668 (64.2%) had medium TBS and 109 (10.5%) had high TBS. TBS was strongly associated with OS; 5-year OS was 39.0% among patients with high TBS compared with 61.1% and 79.4% among patients with medium and low TBS, respectively (p < 0.001). While actuarial survival decreased as time elapsed from resection, CS increased over time irrespective of TBS. The largest differences between 3-year actuarial survival and CS3 were noted among patients with high TBS (5-years postoperatively; CS3: 78.7% vs. 3-year actuarial survival: 30.7%). The effect of adverse clinicopathologic factors including high TBS, poor/undifferentiated tumor grade, microvascular invasion, liver capsule involvement, and positive margins on prognosis decreased over time. Conclusions: CS rates among patients who underwent resection for HCC increased as patients survived additional years, irrespective of TBS. CS estimates can be used to provide important dynamic information relative to the changing survival probability after resection of HCC.